Performance assessment of a microsprinkler - Thomaz, Edivaldo Lopes; Pereira, Adalberto Alves (Acta Scientiarum. Technology, 2014)
Surface hydrological processes are essential to the understanding and prediction of soil erosion. Several equipments are used to measure infiltration rate, runoff and soil loss. However, researchers build their own equipment due to the specific sites where the measurements are performed. This study evaluated the performance of a microsprinkler developed to measure the hydrological processes on unpaved rural roads. The microsprinkler is portable, lightweight, easy to operate, and also low cost. The measured parameters refer to different physical aspects of the rainfall produced as: intensity, drop size, kinetic energy and the simulation area. The microsprinkler was tested at different heights and pressures. The main results obtained: the intensity of simulated rainfall was 71.4 - 148.3 mmh-1, the drop size ranged from 0.3 to 1.2 mm (mean 0.7 mm), the kinetic energy of rainfall varied between 51 and 77% compared with a natural rainfall of similar intensity, and the simulation area had 0.28 - 0.56 m2 (mean 0.40 m2). The parameters obtained in this study are within the limit of others simulators reported in the literature.